Reservoir Characterization of Lower Qamchuqa (Shu'aiba) Formation from the Well BH-86, Bai- Hassan Oil field, Northern Iraq - Shahab, Sabir S.; Baban, Dler H.; Kadhim, Lafta S. (Iraqi Journal of Science, 2022)
The reservoir characterization of Lower Qamchuqa (Shu'aiba) Formation (Aptian) is studied at the well BH-86 of Bai- Hassan Oilfield in Kirkuk area, Northern Iraq. The lithological study (of 91 thin sections) revealed that the formation consists of shaly limestone, a thin bed of marl within the limestone, and dolomitic limestone. Four petrographic microfacies were noticed Lime mudstone microfacies, Dolomudstone microfacies, Lime wackestone microfacies, subdivided into benthonic foraminifera lime wackestone submicrofacies and bioclasts lime wackestone submicrofacies, and the last microfacies is the Lime packstone microfacies, which is subdivided into pelloidal lime packstone submicrofacies and Orbitolina lime packstone microfacies. Shale content is calculated from the gamma-ry log, showing that the formation is mainly of low shale content (less than 35%). The porosity determined from sonic, density, and neutron logs reflect that the range between <1 and 15% and in some intervals about 6% is secondary porosity type. The estimated permeability ranges between <0.01 and 2.0mD, reflecting low permeability. The formation is subdivided into six reservoir units according to the shale content, average porosity, and permeability. The unit RU-5 has the best reservoir properties among the identified units with an average shale content of about 3.15%, about 6.2% porosity, and about 1.75mD average permeability. On the other hand, the least reservoir property is noticed in the unit RU-1 with average 9.48% shale content, 3.64% porosity, and 0.5mD average permeability. The research indicates that the fractures contribute to the flow within the Lower Qamchuqa Formation. Fluids flow through the formation in four unique Hydraulic Flow Units (HFU). Only about 8% of the gross 146m of the formation is expected to have the required reservoir properties for oil production and about 68% for gas production. The actual productive thickness for oil is only about 2.8% of the gross thickness of the studied section, and it’s more than 50% of the gross thickness for gas.